Psychedelic experience and its cognitive function - Nowak, Szymon (Hybris, 2015)
Among the features marking a mystical experience facilitated by certain kind of psychedelic substances researchers singled out the so-called noetic quality, which indicates that mystical experiences can have a cognitive significance. The main goal of my article is then to address the question, whether this cognitive capacity of mystical experience has only a subjective/psychological value, or it should be rather treated as a legitimate kind of cognition. The philosophical aspect of this issue enters the domain of ontology and epistemology, since it concerns the question, whether an object of any cognitive experience has to belong to the physical reality, or a proper cognition can be realized in the reality of symbols. In order to deal with these questions I will refer to the philosophy of H.-G. Gadamer. Even though Gadamer did not investigate altered states of consciousness, I believe his hermeneutics can support a hypothesis that altered states of consciousness provide recognition of reality of symbols.